AlphaB-crystallin regulates remyelination after peripheral nerve injury - Lim, Erin-Mai F. (Proc Natl Acad Sci U S A, 2017)
AlphaB-crystallin (αBC) is a small heat shock protein that is constitutively expressed by peripheral nervous system (PNS) axons and Schwann cells. To determine what role this crystallin plays after peripheral nerve damage, we found that loss of αBC impaired remyelination, which correlated with a reduced presence of myelinating Schwann cells and increased numbers of nonmyelinating Schwann cells. The heat shock protein also seems to regulate the cross-talk between Schwann cells and axons, because expected changes in neuregulin levels and ErbB2 receptor expression after PNS injury were disrupted in the absence of αBC. Such dysregulations led to defects in conduction velocity and motor and sensory functions that could be rescued with therapeutic application of the heat shock protein in vivo. Altogether, these findings show that αBC plays an important role in regulating Wallerian degeneration and remyelination after PNS injury.